An analysis of awe evoked by COVID-19 on green purchasing behavior: A dual-path effect of approach-avoidance motivation - Su, Weihuan; Sun, Xixiang; Guo, Xiaodong; Zhang, Wei; Li, Gen (Frontiers in Psychology, 2022)
Awe has a double valence. However, it has not been tested that the effect of the double valence of awe on green purchasing. In this study, we introduce awe into the context of COVID-19 and construct an "emotion-motivation-behavior" framework, aiming to explore the relationship between the epidemic and green purchasing behavior from a psychological perspective. Study 1 demonstrates the effect of awe on green purchasing and examines the mediating role of the motivation perspective, to reveal the potential different path. Specifically, prosocial motivation mediates the effect of positive awe evoked by COVID-19 on green purchasing; risk avoidance motivation mediates the effect of negative awe evoked by COVID-19 on green purchasing. Study 2 examined the moderating effect of self-construal and explored the boundary conditions of the influence of awe on individual motivation perspective. These findings have important management implications for enterprises to correctly use emotional guidance strategies and promote green marketing practices during the COVID-19.